Effects of a variable light intensity lighting program on the welfare and performance of commercial broiler chickens - Kang, Seong W.; Christensen, Karen D.; Kidd Jr, Michael T.; Orlowski, Sara K.; Clark, James (Frontiers in Physiology, 2023)
Our previous variable-light intensity lighting program studies indicate the light intensity preference behavior of broilers for their daily activity including eating and resting. To evaluate the effects of variable-light intensity lighting program on performance and welfare of broilers, four commercial trials were conducted for looking at behaviors, mortality, leg-health, performance, and brain welfare indicator genes including tryptophan hydroxylase 2 and tyrosine hydroxylase (TH), glucocorticoid receptor (GR), brain-derived neurotropic factor (BDNF), and melanopsin (Opn4) gene expression. One-day-old broilers were housed in four commercial broiler houses. Each quadrant (section) of the house was placed with 4,800 chicks. A total of four lighting programs began on day 7 with 5 lux (lx), 20 lx, natural light (NL, 480 lx), and variable light (2–5/40 lx) using LED lights on a 16L:8D photoperiod. In the variable-light house, the number of dustbathing holes was significantly higher than that in natural-light houses and 5-lx and 20-lx houses. Daily physical activities, footpad condition, fear response to novel objects, body weight, feed conversion ratio, and the number of leg-problem induced culled birds were affected by the variable-light intensity lighting program. Expression of tryptophan hydroxylase 2 in the DRN and VTA of variable-light treated birds was lower than that of 5-lx- and 20-lx-treated birds on day 42 (p < 0.05). Higher expression of VTA-TH in 5-lx-treated birds than that in 20-lx-, NL-, and variable-light-treated birds suggests the high stress-susceptibility of 5-lx treated birds. Lower VTA-GR expression in 20-lx- and variable-light-treated birds indicates lower stress than that in NL- and 5-lx-treated birds (p < 0.05). The VTA-BDNF expression of NL-treated birds was 2.5 fold higher than that of 5-lx-, 20-lx-, and variable-light-treated birds (p < 0.05), and variable-light-treated birds showed the lowest level of BDNF expression (p < 0.05), suggesting the chronic social defeat stress in NL-treated birds. The result of VTA-Opn4 expression on day 42 suggests the possible role of VTA-Opn4 in broiler welfare through central light perception. Taken together, the variable-light intensity lighting program increased volunteer natural behaviors and physical activity, which may improve footpad condition and leg health of birds, consequently. Performance data including the increased daily weight gain and the lowered feed conversion ratio and results of brain welfare indicator gene expression showed the beneficial effect of the variable-light intensity lighting program on the performance and welfare of commercial broilers.